Trigeminal neuralgia: bibliometric analysis of the fifty top-cited articles in the period 2000-2016 - Yasmany Fornaris-Cedeño; Ibraín Enrique Corrales-Reyes; Caridad de Jesús Pérez-Martínez (Universidad de Concepción., 2018)
Objective: To analyze the fifty top-cited articles on trigeminal neuralgia during the period 2000-2016. Methods: A bibliometric study using Harzing's Publish or Perish 5 software and Google Scholar as the database was performed. The term used in the search was "trigeminal neuralgia." A list was generated with the 50 top-cited articles in the period 2000-2016 and variables of interest were studied. Results: The articles received 12316 citations with a mean of 724.47 and 246.32 citations per year and per articles, respectively. The article with the highest mean number of citations/year (48.57) was published by Cruccu et al., in 2010. The articles had an h index of 48 and were published in 24 scientific journals. The journals with the highest number of articles were Neurology and Journal of Neurosurgery, with 7 articles each (14%). A prevalence of North American authorship was observed (n=14; 28.0%). Original articles (n=26; 52.0%) and papers written by six authors (n=12; 24.0%) were also the most prevalent. The highest number of articles by a binomial international collaboration was from Austria-Italy (n=3; 6.00%). The most researched topics were related to updates in specific treatments for trigeminal neuralgia and neuropathic pain in general. Conclusions: The most cited article was published in 2010 in the European Journal of Neurology. Articles published in the years 2001 and 2002 received the highest number of citations. The most relevant scientific collaborations were observed between Italian and Austrian researchers.